Aplicações da cultura de tecidos vegetais em plantas medicinais nativas da Amazônia - SANTOS, Milena Áurea Santana dos (Universidade Federal do Oeste do Pará, 2024)
Brazil is considered the country with the greatest biodiversity of the planet, it houses numerous medicinal plants with remarkable therapeutic properties, as is the case of the Amazon. These plants are often collected in a predatory and indiscriminate manner, which can make them vulnerable to extinction. In addition to predatory collection, the use of medicinal plants as raw material can be compromised by factors such as heterogeneity of individuals, genetic and biochemical variability, seasonality and difficulty of propagation. As an alternative to these problems, plant tissue culture consists of cultivating, in vitro, cells, tissues or plant organs under aseptic conditions. In this context, the present study aimed to carry out a bibliographical survey on the applications of tissue culture techniques in medicinal plants native to the Amazon. Indexed databases such as Google Scholar, Scielo and Periodicals of CAPES were consulted. According to the bibliographical survey carried out, it was verified that the use of tissue culture techniques with medicinal plants native to the Amazon is still incipient. Among the techniques, micropropagation was the most employed, mostly only studies performed until the asepsis and culture establishment phase. From the literature consulted, only three articles carried out studies on somatic embryogenesis and only one, was successful in regeneration. Similarly, few studies have performed in vitro establishment isolating zygotic embryos. It was also verified that the studies are still focused on callus and no study on suspension culture was found and only two with use of bioreactors. For in vitro drug production it is necessary to obtain callus and these are cultivated in liquid medium under agitation in suspension or bioreactor culture. Considering that the studies are still incipiente, the enormous bottleneck of research regarding the use of tissue culture techniques for medicinal plants indigenous to the Amazon region becomes evident.